Comparative characteristics of typical and atypical (Mycoplasma) pneumonia in children - T. A. Britkova; N. V. Gudovskikh; M. S. Chupina (LLC "Diagnostics and Vaccines", 2021)
Aim: To compare the features of clinical-anamnestic and laboratory-instrumental data and treatment of children with typical and atypical (Mycoplasma) forms of pneumonia.Materials and methods. A comparative analysis was carried out of 1 70 case histories of children in hospital with a verified diagnosis of pneumonia in 2020. The basis for the diagnosis of Mycoplasma pneumonia was a positive PCR result of a smear of the posterior pharyngeal wall. The resulting data was constructed using Microsoft Excel 2007.Results. Mycoplasma pneumonia is specific for older schoolchildren; characterized by: prolonged course (73.5%), long-term preservation of an unproductive cough (75.7%), mild intoxication (68.6%) and catarrhal syndromes (54.3%), gradual onset (76.6%), severe lymphocytosis up to 55%, segmental or polysegmental damage to the lung tissue (92.7%).